Foliar zinc oxide nanoparticles, and salicylic acid on tomato growth, productivity, and fruit quality under drought stress conditions (Bioagro, 2026)
This study aimed to evaluate the effectiveness of zinc oxide nanoparticles (ZnO-NPs) and salicylic acid (SA), applied individually or in combination, in alleviating the adverse effects of water deficit conditions at 50 and 75 % field capacity (FC) on the growth performance and yield of tomato plants (cv. Super Strain). The results showed that water stress at 50 and 75 % FC adversely affected various vegetative parameters i.e. plant height, leaf area, dry weight, and yield factors. Fruit yield decreased by 24.78 and 54.16 % in 2022, and 27.91 and 60.06 % in 2023, respectively. Additionally, water deficiency led to reduced chlorophyll levels and lower relative leaf water content in both seasons. Applying ZnO-NPs and SA as foliar treatments, individually or in combination, successfully reduced the adverse effects of water stress on tomato plants. This treatment resulted in improved plant growth, chlorophyll content, leaf relative water content, and fruit yield. The joint use of ZnO-NPs and SA delivered superior performance in counteracting the adverse effects of water stress on most evaluated traits, exceeding the benefits observed with either treatment alone. Notably, fruit yield increased by 21.25 and 43.57 % at 50 and 75 % field capacity in 2022, and by 24.67 and 74.44 % in 2023, respectively.
Keywords: Firmness; phenols; relative water content; total soluble solids; vitamin C